Statistical Decision Models for Brokering - Bracken, Jerome; Soland, Richard M. (Management Science, 1969)
Statistical decision models are formulated for a decision situation involving a decision maker who is a broker, a person engaged in bringing together sellers and buyers to make transactions. The objective of the analysis is the determination of a plan in accordance with the broker's subjective estimates which can serve as a guide for optimally allocating his energies.